Quantification of the sources of soluble organic N (SON) from new litter or indigenous soil in a typical subtropical forest. (21st February 2021) - Ding, Xianqing; Chang, Yue; Hou, Hongbo; Peng, Peiqin; Xiang, Wenhua
Abstract: Decomposition of forest litter plays a major role in nitrogen (N) dynamics in soil. However, the effect of new litter on indigenous soil N and its contribution to soil N in natural forest remains unknown. An in situ soil column experiment was conducted and 15 N labelled litter was added to decompose for 14 months to examine the effect of litter retention on soil N dynamics in a typical subtropical forest. Litter removal in the soil column was used as a control. The results showed that litter removal caused a continuous decrease in concentration of soil soluble organic N (SON) in the first 5 months (August in 2018‐January in 2019), and SON concentration went up in the eighth month. Litter retention accelerated the reduction of soil SON concentration in the first 2 months, and SON concentration maintained a high value after that period. Soil NH4 + ‐N derived from litter was nitrified rapidly, and the newly formed NO3 − ‐N was quickly immobilized or lost. Only 1.8% of soil SON came from litter N and 98.2% from indigenous soil N under the decomposition of labelled litter. Litter provided N to form new soil SON continuously, however, only a small part of SON was relatively stable. Soil SON and total N (TN) are formed after long‐term litter accumulation and decomposition, and litter retention plays an important role in soil N dynamics.